Computational study of synthetic and natural polymer additives — Antioxidant potential of BHA, TBHQ, BHT, and curcumin. (July 2022) - Thbayh, Dalal K.; Fiser, Béla
Highlights: Antioxidant potential of one natural and three synthetic additives have been compared. In general, O-H bonds are weaker than C-H in all species. BHT is the best radical scavenger within the studied set of species. The ranking of the species is the following: BHT > BHA ≈ TBHQ > curcumin A > curcumin D. Abstract: The antioxidant potential of commonly used synthetic and natural antioxidant additives, including butylated hydroxytoluene (BHT), butylated hydroxyanisole (BHA), tert ‑butylhydroquinone (TBHQ), and natural additive, curcumin have been studied and compared by calculating the bond dissociation enthalpy (BDE), ionization potential (IP), proton dissociation enthalpy (PDE), proton affinity (PA), and electron transfer enthalpy (ETE) values for each potential hydrogen donor site. The results indicate that, in each additive an OH group has the highest antioxidant potential (lowest BDE value). The studied molecules can be ranked based on their antioxidant potential as follows: BHT > BHA ≈ TBHQ > curcumin A > curcumin D. By comparing with commonly used polymers, in each studied species, there is at least one X-H bond which has a lower BDE value than in the corresponding polymeric material. Thus, all studied additives are potentially applicable to protect polymeric materials. BHT is the best radical scavenger additive in case of the hydrogen atom transfer (HAT), and the sequential proton loss electron transfer (SPLET) mechanisms to donate a H atom, but in single electron transfer proton transfer (SETPT) curcumin could also be suitable.